Further investigation of safety monitoring guidelines based on magnetic resonance imaging lesion activity in multiple sclerosis clinical trials. (January 2015) - Dong, Jing; Zhao, Yinshan; Petkau, A John; Li, David KB; Riddehough, Andrew; Traboulsee, Anthony
We assess two modified guidelines for monitoring patient safety in multiple sclerosis (MS) trials. These guidelines flag patients with an increase in contrast enhancing lesion (CEL) count above a threshold over the CEL level 1–2 months earlier. We compare the new guidelines to the original guideline where the threshold is set according to the baseline by applying the guidelines to two previous studies. The odds ratios of a subsequent clinical relapse associated with meeting the CEL threshold based on the modified guidelines are similar to those based on the original guideline. There is a need for patient and cohort specific monitoring procedures.